Warm‐air advection, air mass transformation and fog causes rapid ice melt. Issue 13 (4th July 2015) - Tjernström, Michael; Shupe, Matthew D.; Brooks, Ian M.; Persson, P. Ola G.; Prytherch, John; Salisbury, Dominic J.; Sedlar, Joseph; Achtert, Peggy; Brooks, Barbara J.; Johnston, Paul E.; Sotiropoulou, Georgia; Wolfe, Dan
Abstract Direct observations during intense warm‐air advection over the East Siberian Sea reveal a period of rapid sea‐ice melt. A semistationary, high‐pressure system north of the Bering Strait forced northward advection of warm, moist air from the continent. Air‐mass transformation over melting sea ice formed a strong, surface‐based temperature inversion in which dense fog formed. This induced a positive net longwave radiation at the surface while reducing net solar radiation only marginally; the inversion also resulted in downward turbulent heat flux. The sum of these processes enhanced the surface energy flux by an average of 15 W m−2 for a week. Satellite images before and after the episode show sea‐ice concentrations decreasing from > 90% to 50% over a large area affected by the air‐mass transformation. We argue that this rapid melt was triggered by the increased heat flux from the atmosphere due to the warm‐air advection.